The Role of Organizational Communication to Improve the Performance of Dormitory Supervisors at The Raudhatus Salaam Islamic Boarding School - Rahma Wati, Miftakhul Jannah; Irfanudin, Fahmi (Journal of Islamic Communication and Counseling, 2024)
This study’s objective is to determine the role of organizational communication in improving the performance of dormitory supervisors in coaching OSANTRAS. This qualitative research applied a case study approach, and the data analysis used descriptive analytics. The subjects in this study were the leaders of the boarding school, 2 dormitory supervisors, and 2 students who were members of OSANTRAS. The data collection process was carried out by means of observation, interviews, and documentation. The results of this study indicate that organizational communication at the Raudhatus Salaam Islamic Boarding School has been going well, as indicated by the leaders who establish communication with all stakeholders in the Islamic boarding school, be it teachers, employees, supervisors, and students. This research also reveals that the supporting factors in improving the performance of dormitory supervisors are productive meetings and good cooperation. Meanwhile, the inhibiting factor is the frequent change of dormitory supervisors.